2023
DOI: 10.1021/acssynbio.2c00619
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Editing Efficiency of CRISPR-Cas9 by Reducing the Generation of Escapers Based on the Surviving Mechanism

Abstract: Due to the high specificity in targeting DNA and highly convenient programmability, CRISPR-Cas-based antimicrobials applied for eliminating specific strains such as antibiotic-resistant bacteria in the microbiome were gradually developed. However, the generation of escapers makes the elimination efficiency far lower than the acceptable rate (10–8) recommended by the National Institutes of Health. Here, a systematic study was carried out providing insight into the escaping mechanisms in Escherichia coli, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In particular, as a consequence of the SOS response triggered by Cas9-mediated double strand breaks (DSB), mutations can occur in the CRISPR circuitry or in the target gene 19,20,[22][23][24] . Indeed, it has been reported that escapers can occur at a rate higher than the one considered as acceptable by the National Institute of Health 25 , hindering the application of CRISPR-based antimicrobials in clinical settings. In the field of antimicrobial resistance, CRISPR-escape mutants that have evolved target gene mutations are of specific concern since the new generated sequence became immune to CRISPR targeting and may still encode a functional protein, thus representing a new resistance variant.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, as a consequence of the SOS response triggered by Cas9-mediated double strand breaks (DSB), mutations can occur in the CRISPR circuitry or in the target gene 19,20,[22][23][24] . Indeed, it has been reported that escapers can occur at a rate higher than the one considered as acceptable by the National Institute of Health 25 , hindering the application of CRISPR-based antimicrobials in clinical settings. In the field of antimicrobial resistance, CRISPR-escape mutants that have evolved target gene mutations are of specific concern since the new generated sequence became immune to CRISPR targeting and may still encode a functional protein, thus representing a new resistance variant.…”
Section: Introductionmentioning
confidence: 99%
“…(2) These nucleases can also be used in combination with a compatible exogenous recombinase (e.g., lambda Red for Escherichia coli) in which the Cas nucleases were used to counterselect against unedited cells 12,[16][17][18][19] . However, the efficient DNA cleavage with Cas nucleases under both cases may lead to massive cell death and a low transformation efficiency [20][21][22][23] . In addition, currently available genome editing tools, including most Cas9 and Cas12 nucleases are tolerant to single mismatches in the target regions 4,7,[24][25][26][27][28][29] , therefore these nucleases may efficiently target mismatched sites, hindering their applications in homology-directed single nucleotide editing (SNE).…”
mentioning
confidence: 99%